<span>2(3)× = 3×+1 is equal when f(x) = g(x).
f(x) is equal to g(x) when x = 0.
Therefore, the solution to the equation </span><span>2(3)×=3×+1 is x = 0.</span>
Answer:
(a)
![V=x^3+x^2-9x-9](https://tex.z-dn.net/?f=V%3Dx%5E3%2Bx%5E2-9x-9)
(b)
![x=10](https://tex.z-dn.net/?f=x%3D10)
(c)
![x=\frac{7}{2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B7%7D%7B2%7D)
Step-by-step explanation:
we are given
length is x+1
![L=x+1](https://tex.z-dn.net/?f=L%3Dx%2B1)
width is x+3
![W=x+3](https://tex.z-dn.net/?f=W%3Dx%2B3)
height is x-3
![H=x-3](https://tex.z-dn.net/?f=H%3Dx-3)
(a)
we can use volume formula
![V=L\times W\times H](https://tex.z-dn.net/?f=V%3DL%5Ctimes%20W%5Ctimes%20H)
now, we can plug it
![V=(x+1)\times (x+3)\times (x-3)](https://tex.z-dn.net/?f=V%3D%28x%2B1%29%5Ctimes%20%28x%2B3%29%5Ctimes%20%28x-3%29)
now, we can simplify it
![V=x^3+x^2-9x-9](https://tex.z-dn.net/?f=V%3Dx%5E3%2Bx%5E2-9x-9)
(b)
we are given volume =1001
so, we can set V=1001
and then we can solve for x
![V=x^3+x^2-9x-9=1001](https://tex.z-dn.net/?f=V%3Dx%5E3%2Bx%5E2-9x-9%3D1001)
now, we can factor it
![\left(x-10\right)\left(x^2+11x+101\right)=0](https://tex.z-dn.net/?f=%5Cleft%28x-10%5Cright%29%5Cleft%28x%5E2%2B11x%2B101%5Cright%29%3D0)
![x-10=0](https://tex.z-dn.net/?f=x-10%3D0)
![x=10](https://tex.z-dn.net/?f=x%3D10)
(b)
we are given volume
so, we can set
![V=14\frac{5}{8}=\frac{14\times 8+5}{8}](https://tex.z-dn.net/?f=V%3D14%5Cfrac%7B5%7D%7B8%7D%3D%5Cfrac%7B14%5Ctimes%208%2B5%7D%7B8%7D)
![V=\frac{117}{8}](https://tex.z-dn.net/?f=V%3D%5Cfrac%7B117%7D%7B8%7D)
and then we can solve for x
![V=x^3+x^2-9x-9=\frac{117}{8}](https://tex.z-dn.net/?f=V%3Dx%5E3%2Bx%5E2-9x-9%3D%5Cfrac%7B117%7D%7B8%7D)
now, we can factor it
![8x^3+8x^2-72x-189=0](https://tex.z-dn.net/?f=8x%5E3%2B8x%5E2-72x-189%3D0)
![\left(2x-7\right)\left(4x^2+18x+27\right)=0](https://tex.z-dn.net/?f=%5Cleft%282x-7%5Cright%29%5Cleft%284x%5E2%2B18x%2B27%5Cright%29%3D0)
![2x-7=0](https://tex.z-dn.net/?f=2x-7%3D0)
![x=\frac{7}{2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B7%7D%7B2%7D)
Answer:
hmmmmmmmmm
Step-by-step explanation:
$12?
i think
Answer:
please mark me as brainlest
Step-by-step explanation:
B is the answers for the question
Answer:
A zero-order table is simply a table showing variables
controlled for. As an example, given an equation of two variables,
this table shows the values that result from the available values
for those two variables.